Analisis Pembebasan Pemenuhan Prestasi Akibat Adanya Overmacht Karena Corona Virus Disease 2019 (Covid-19) Di Indonesia - Rachma Ayu Kusuma Dewi; Amelia Bellatrix Pantjo'u; Widya Dika Chandra; Sa'baniah Sa'baniah (Jurnal Selat, 2020)
Corona Virus Disease 2019 or commonly referred to as Covid-19 is a disease that attacks almost the entire world, including Indonesia. Covid-19 has caused many social and economic impacts, one of which is related to the fulfillment of achievements arising from a contract. Of course, Covid-19 is an unexpected event, which hinders the fulfillment of the achievements in the contract. This then makes the parties who cannot fulfill the achievement postulate Covid-19 as a force majeure to be free from the fulfillment of these achievements. Based on this background, this study aims to find out 1) Whether Covid-19 can be used as an excuse for force majeure, and 2) What are the consequences of Covid-19's law as an force majeure? This research is a legal study using a statutory approach and a conceptual approach. Based on this research, it was found that Covid 19 is a force majeure because it meets the requirements of an event that can be said to be an overmacht and is affirmatively verified in several laws and regulations, such as Law 24/2007, Perpu 1/2020, and KEPKABNPB 13.A / 2020 . The legal consequences arising from Covid-19 is force majeure are 1) creditors cannot request fulfillment of achievements, 2) debtors cannot be declared negligent, so there is no need to pay compensation, and 3) creditors cannot ask for termination agreement.